Research Methods for Cultural Studies (Edinburgh University Press, 2008)
This new textbook addresses the neglect of practical research methods in cultural studies. It provides students with clearly written overviews of research methods in cultural studies, along with guidelines on how to put these methods into operation. It advocates a multi-method approach, with students drawing from a pool of techniques and approaches suitable for their own topics of investigation.